Biodegradability and mechanism of florfenicol via Chlorella sp. UTEX1602 and L38: Experimental study. (January 2019) - Song, Chunfeng; Wei, Yanling; Qiu, Yiting; Qi, Yu; Li, Yang; Kitamura, Yutaka
Graphical abstract: Highlights: Biodegradability of florfenicol via two kinds Chlorella sp. was investigated. Florfenicol could be removed by Chlorella L38 with removal ratio above 95%. Chlorella L38 could grow with low inhibition rate under the high concentration of florfenicol. Florfenicol biodegradation was the dominant pathway via microalgae purification. Abstract: In this work, florfenicol removal via two kinds Chlorella sp. ( UTEX1602 and L38 ) was investigated. The experimental results indicated that FF could be removed by biodegradation associated with microalgae growth. Compared to Chlorella sp. UTEX1602, L38 had a good self-adjustment capacity at the condition of high initial FF concentration. The biodegradation of FF followed the first order kinetic model with half-lives ranged from 3.53 to 7.63 days at different initial concentration. The removal efficiency of FF could achieve 97% when the FF concentration was set at 46 mg·L −1 . While the FF concentration in the medium increased to 159 mg·L −1, more than 74% FF could still be purified via Chlorella sp. L38 . Therefore, Chlorella sp. L38 could be promising alternative algae to be used for FF removal from different water sources.